Design of single layered circular and rectangular U-slotted, CPW-fed antennas and arrays for RFID applications - Roshayati, M.; Soh, Ping Jack; Ismahayati, Adam (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/